Trade Policy Reform and Poverty Alleviation - Hoekman, Bernard; Michalopoulos, Constantine; Schiff, Maurice; Tarr, David (World Bank, Washington, DC, 2014)
In this paper, developed as part of the World Bank's Poverty Reduction Strategy Sourcebook, the authors examine how to implement trade liberalization as part of a strategy for alleviating poverty in developing countries. They discuss trade policy instruments, institutions, complementary policies, sector issues, adjustment policies, and safety nets in an integrated approach to trade policy as a tool for poverty alleviation. The authors examine the patterns or models of trade policy that have been successful in alleviating poverty. They discuss the role of tariffs, nontariff barriers, contingent protection (such as safeguards and antidumping), special import regimes (such as duty drawback), export taxes, export subsidies, and trade-related institutions (such as standards, marketing, export finance, customs clearance, and regional trade arrangements). The authors also discuss policies that complement successful trade reform, including macroeconomic stability, a competitive exchange rate, flexible labor markets, competitive product markets, and policies that do not discriminate against foreigners in investment. They suggest approaches to policies and institutions in services and agriculture, key sectors in poverty reduction. They explain the roles of retraining and safety nets in dealing with the adjustment costs of trade liberalization. Finally, the authors elaborate guidelines for implementing trade reform and explain tools for assessing whether trade reform will help or harm the poor in particular sectors in the short run.